Cardiovascular effects, induction and recovery characteristics and alfaxalone dose assessment in alfaxalone versus alfaxalone-fentanyl total intravenous anaesthesia in dogs. (November 2017) - Dehuisser, Virginie; Bosmans, Tim; Kitshoff, Adriaan; Duchateau, Luc; de Rooster, Hilde; Polis, Ingeborgh
Abstract: Objective: To compare cardiovascular effects and anaesthetic quality of alfaxalone alone or in combination with a fentanyl constant rate infusion (CRI) when used for total intravenous anaesthesia (TIVA) in dogs. Study design: Prospective, blinded, randomized, experimental study. Animals: A group of 12 intact female dogs. Methods: Following intramuscular dexmedetomidine (10 μg kg −1 ) and methadone (0.1 mg kg −1 ) administration, anaesthesia was induced intravenously with alfaxalone (2 mg kg −1 ) (group AP) or alfaxalone (2 mg kg −1 ) preceded by fentanyl (2 μg kg −1 ) (group AF). Anaesthetic maintenance was obtained with an alfaxalone variable rate infusion (VRI) started at 0.15 mg kg −1 minute −1 (group AP) or an alfaxalone VRI (same starting rate) combined with a CRI of fentanyl (10 μg kg −1 hour −1 ) (group AF). The alfaxalone VRI was adjusted every 5 minutes, based on clinical assessment. Cardiovascular parameters (recorded every 5 minutes) and recovery characteristics (using a numerical rating scale) were compared between groups. A mixed model statistical approach was used to compare the mean VRI alfaxalone dose and cardiovascular parameters between groups; recovery scores were analysed using the Wilcoxon rank-sum test (α = 0.05). Results: The mean CRI alfaxalone dose for anaesthetic maintenance differed significantly between treatments [0.16 ± 0.01 mg kg −1 minute −1 (group AP) versus 0.13 ± 0.01 mg kg −1 minute −1 (group AF)]. Overall heart rate, systolic, mean and diastolic arterial pressures were lower in group AF than in group AP ( p < 0.0001, p = 0.0058, p < 0.0001 and p < 0.0001, respectively. Recovery quality scores did not differ significantly and were poor in both groups. Conclusions and clinical relevance: In combination with a fentanyl CRI, an alfaxalone TIVA provides a cardiovascular stable anaesthesia in dogs. The addition of fentanyl results in a significant dose reduction. The quality of anaesthetic recovery remains poor.